Using Guided Inquiry-Based Electronic Science Worksheets Assisted by Virtual Laboratories on the Science Process Skills of Middle School Students - Miftahul Jannah; Zuhdan Kun Prasetyo; Shanty Yustin Ungirwalu (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
Science Process Skills (PPP) are important skills for students to have in science learning. However, the PPP of students is still lacking, characterized by the lack of ability of students in formulating hypotheses, ferferencing, collecting and processing data, and concluding in the learning process. The provision of electronic science LKPD teaching materials based on guided inquiry assisted by virtual laboratories that can support PPP is one of the solutions to train and improve students' PPP. This study aims to analyze the effectiveness of electronic science LKPD based on guided inquiry assisted by virtual laboratory on the improvement of student PPP. This research method uses a quantitative method. The research design used is One Group Pretest-Posttest Design. The sample used was 32 students in grade VIII of junior high school. The data collection technique uses the PPP test with 15 pretest and posttest question instruments. The data obtained was analyzed using the parametric statistics of the Paired-Sample T-Test test, showing a significant difference between the average PPP of students before and after the administration of the guided inquiry-based electronic science LKPD assisted by a virtual laboratory. The average difference was then tested in effect size with the results of the electronic LKPD of science based on guided inquiry assisted by a virtual laboratory had a great effect on increasing students' PPP. This research has implications for science learning with the use of technology-assisted teaching materials.